The Situation of Crisis Management in the Holy Capital Secretariat in Light of the Corona Covid-19 Pandemic and its Impact on the Community Service During the Years (2019 to 2020) - Al-Osaimi, Muwaffaq Ahmed (Journal of Risk and Crisis Management, 2024)
The current study aims to identify the situation of crisis management in the Holy Capital Municipality in light of the Covid-19 pandemic, in an effort to provide quality service to the community, provide the community partnership and exchange of experiences. The study society consists of (2000) persons working in the secretariat of the Holy Capital. The study sample includes 214 persons (153 administrative employees and 61 managers). They are chosen randomly by distributing a link to the questionnaire on the study society. The researcher uses a questionnaire tool designed by himself. The findings are as follows: The situation of the crisis management in the Holy Capital Municipality in light of the Covid-19 pandemic and its impact on the general plans of the Capital Municipality shows a high degree of impact. The role of crisis management in the Municipality of the Holy City in light of the crisis of the Covid-19 pandemic, and the impact of this management on the quality of service provided by the Municipality of the Capital shows a high degree. As well as the role of crisis management in the Municipality of the Holy Capital in light of the crisis of the Covid-19 pandemic and its impact on the Secretariat’s service to the community, community partnership and exchange of experiences also shows a high degree. While the axe of the challenges facing the Capital Municipality in light of its current crisis management and its impact on the quality of administrative service, providing community service, community partnership and exchange of experiences shows a medium degree. There are no statistically significant differences in the study axes that are attributed to the work experience variable. There are statistically significant differences in the first, second, and third axis. The differences are among the postgraduate qualification (Master’s, PhD) and the secondary qualifications. The differences are in favor of the postgraduate qualification. There are no statistically significant differences in the fourth axis.